Implementasi Prinsip Lembaga Keuangan Syariah pada BTPN Syariah KCS Pekanbaru - Muhammad Revan; Azwar Azwar; Mildah Mildah; Imam Daruqutni Al Hasymi; Ayub Syaputra; Putri Nadhea (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study examines the implementation of Islamic financial institution principles in the operational activities of BTPN Syariah KCS Pekanbaru. Islamic banking plays a strategic role not only as a financial intermediary institution but also as an institution that applies Islamic values and ethical principles in every economic activity. This research aims to analyze the implementation of sharia contracts, fundraising products, financing products, and the application of sharia principles in the operational practices of BTPN Syariah KCS Pekanbaru. The study employed a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation involving relevant bank personnel and supporting documents. The findings indicate that BTPN Syariah KCS Pekanbaru consistently implements sharia principles in fundraising and financing activities through the application of wadiah, mudharabah, murabahah, and musyarakah contracts. The bank also avoids transactions containing elements of riba, gharar, and maysir, ensuring that all operational activities comply with Islamic law. Furthermore, the bank applies the principles of profit sharing, transparency, accountability, trustworthiness, and fairness in serving its customers. These practices demonstrate consistency between the theoretical concepts of Islamic financial institutions and their practical implementation in daily banking operations. Therefore, BTPN Syariah KCS Pekanbaru can be categorized as an Islamic financial institution that consistently upholds Islamic principles while supporting sustainable financial services and strengthening public confidence in the Islamic banking system.